Caminhos de permanência : a resistência e o modo de vida dos quilombos de Banguelas em Prainha (PA) - Cabral Junior, Fernando O'Grady (My University, 2025)
This work aims to analyze the dynamics of the way of life and the historical resistance of the quilombola communities in Prainha, seeking to present the cultural, social, economic, and environmental practices that characterize the community. From a methodological perspective, this research is anchored in Cultural History and adopts a qualitative approach, using techniques such as questionnaires, field observation, and document analysis. To obtain the necessary information and adequately address the investigative questions, visits were made to the Banguelas community, located on the banks of the Caminaú River, between December 2023 and February 2024. During these visits, interviews and observations were conducted in homes, ovens, cultivated areas, the school, chapel, and along the lake's shores, where relevant activities for the community take place. In the field, it was observed that the pioneers of this community, from the beginning, longed to restore family ties and gain the freedom to build relationships free from external influences, shaping the values and practices that guide community life to this day. The community, therefore, places special value on its intangible assets, such as life teachings, family harmony, and the freedom that flourishes in its locality, which are present in the bonds between members, in the preservation and transmission of their cultural traditions, and in the care for natural resources, which are maintained through sustainable management practices. In this regard, although expressive cultural activities continue to occupy a central place in the life of the community, there has been a shift in the religious sphere, as while the ancestors adopted Afro-Brazilian practices, today, the community is exclusively Catholic. Nevertheless, the traditions and rituals that shaped the cultural identity of the ancestors have left a lasting influence on local celebrations. In terms of subsistence, the community continues to follow traditional methods, such as the cultivation of crops and the extractive exploitation of fruits. Besides these practices, knowledge is transmitted through family-based education, passed down from generation to generation, as well as through access to formal educational institutions. In this context, the educational product developed as part of this dissertation, materialized in the form of a booklet, plays an important role, as it documents and values the cultural and historical heritage of the Banguelas quilombola community, in addition to serving as a pedagogical resource. [resumo fornecido pelo autor]
O presente trabalho tem como objetivo analisar as dinâmicas do modo de vida e a resistência histórica das comunidades quilombolas em Prainha, buscando apresentar as práticas culturais, sociais, econômicas e ambientais que caracterizam a comunidade. Do ponto de vista metodológico, esta pesquisa está ancorada na História Cultural e adota uma abordagem qualitativa, fazendo uso de técnicas como questionário, observação em campo e análise documental. Para a obtenção das informações necessárias e o devido atendimento às questões investigativas, foram realizadas visitas à comunidade dos Banguelas, situada às margens do rio Caminaú, entre dezembro de 2023 a fevereiro de 2024. Durante essas visitas, foram conduzidas entrevistas e observações nas residências, fornos, áreas cultivadas, escola, capela e nas margens do lago, onde se desenvolvem atividades relevantes para a comunidade. Em campo, verificou-se que os precursores desta comunidade, desde o princípio, ansiavam por restabelecer os vínculos familiares e conquistar a liberdade para construir relações livres de influências externas, que moldou os valores e as práticas que orientam a vida comunitária até os dias atuais. A comunidade, portanto, valoriza de maneira especial os seus bens imateriais, como os ensinamentos de vida, a harmonia familiar e a liberdade que floresce em sua localidade, estando presente nos laços entre os membros, na preservação e transmissão de suas tradições culturais e no cuidado com os recursos naturais, que são mantidos por meio de práticas sustentáveis de manejo. Nesta senda, atualmente, embora as atividades culturais expressivas continuem a ocupar um espaço central na vida da comunidade, houve uma mudança no âmbito religioso, pois, enquanto os antepassados adotavam práticas de raízes Afro-Brasileiras, hoje, a comunidade é exclusivamente católica. Ainda assim, as tradições e os rituais que marcaram a identidade cultural dos ancestrais deixaram uma influência duradoura nas celebrações locais. Em termos de subsistência, a comunidade continua a seguir métodos tradicionais, como o cultivo de roçados e a exploração extrativista de frutos. Além dessas práticas, a transmissão do conhecimento ocorre através de uma educação de cunho familiar, passada de geração em geração, bem como pelo acesso a instituições formais de ensino. Nesse contexto, o produto educacional desenvolvido como parte integrante desta dissertação, materializado na forma de uma cartilha, assume um papel importante, visto que documenta e valoriza a herança cultural e histórica da comunidade quilombola dos Banguelas, além de servir como um recurso pedagógico. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Quilombos - Prainha (PA) - História; Quilombolas - Prainha (PA) - Aspectos culturais; Quilombolas - Prainha (PA) - Usos e costumes; Negros - Prainha (PA) - Identidade étnica; History - Study and teaching; Quilombos - Prainha (Brazil) - History; Quilombos - Prainha (Brazil) - Cultural aspects; Quilombos - Prainha (Brazil) - Social life and customs; Blacks - Prainha (Brazil) - Ethnic identity